2016
DOI: 10.18282/amor.v2.i1.83
|View full text |Cite
|
Sign up to set email alerts
|

Lysophosphatidic acid receptor isoforms expression in prostate cancer cells is differentially regulated by the CYP17A1 inhibitor abiraterone and depends on the androgen receptor

Abstract: Prostate cancer (PC) treatment with steroid synthesis inhibitor, abiraterone acetate, (AA) provides substantial survival advantages in advanced PC therapy. Owing to AA's anti-proliferative efficacy, even in the absence of androgen receptor (AR), the molecular mode of action is suspected to be a result of simultaneously targeted cellular factors. The present study demonstrated a differentially regulated expression of proliferative lysophosphatidic acid receptor (LPAR) isoforms in androgen receptor (AR)-positive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Interestingly, one report suggested that LPAR1 expression in androgen receptorexpressing prostate cancer cells is regulated in an androgen-dependent manner [51]. In comparison with LPARs 1-3, little is known about LPAR4 and LPAR5 as they are expressed at low levels in prostate cancer cells [52].…”
Section: Prostate Cancermentioning
confidence: 99%
“…Interestingly, one report suggested that LPAR1 expression in androgen receptorexpressing prostate cancer cells is regulated in an androgen-dependent manner [51]. In comparison with LPARs 1-3, little is known about LPAR4 and LPAR5 as they are expressed at low levels in prostate cancer cells [52].…”
Section: Prostate Cancermentioning
confidence: 99%
“…The current issue of AMOR features an interesting article by Mandelkow and co-workers [5] , which explores the in vitro activity of abiraterone acetate against the androgen receptor in prostate cancer cells and this may lead to the invention of innovative methods to help personalize the administration of this drug. Advocating the use of personalized therapy in the treatment of prostate cancer should be the focus of basic and clinical researchers alike as this should, in principle, improve the prognosis of cancer patients.…”
Section: Receivedmentioning
confidence: 99%